Relationship between Serum Tumor Markers, CA-125, CEA, CA19-9, LDH, and βHCG with Histopathology and Age in Women with Ovarian Tumors - Bagde, Nilajkumar D; Bagde, Madhuri N; Lone, Zamir A (Asian Pacific Journal of Cancer Biology, 2020)
Introduction: Ovarian tumors pose a diagnostic predicament as it is difficult to differentiate benign from malignant without a histopathology report. Appropriate tumor markers may serve as diagnostic aid to better decision making in the management of these cases. We attempted to determine the relationship between age, serum markers, and histopathological sub types of ovarian tumors to help distinguish benign from malignant tumors. Methods: A retrospective cross sectional study of all cases with ovarian tumors that had available histopathology reports and tumor marker levels was done at a single centre. Variables examined were age, histopathology report and serum tumor markers CA-125, CEA, CA19-9, LDH, and βHCG. Results: Histopathological analysis revealed 26% teratomas, 28% cystadenomas, 14% corpus luteal cysts, 26% carcinomas and 6% endometriomas. CA-125 was the only marker that was significantly raised in malignant versus benign tumors (p=0.008) and increased with increasing age. All women with raised CEA reports had teratomas, and none with cancers had a raised CEA. CA19-9, LDH and βHCG were not significantly different in benign versus malignant tumors. Conclusions: CA-125 may be used as an adjuvant diagnostic tool for ovarian cancer in older women. The role of CEA as a marker for teratomas needs further evaluation.